NSCs Under Strain—Unraveling the Mechanoprotective Role of Differentiating Astrocytes in a Cyclically Stretched Coculture With Differentiating Neurons - Abraham, Jella-Andrea; Blaschke, Stefan; Tarazi, Samar; Dreissen, Georg; Vay, Sabine U.; Schroeter, Michael; Fink, Gereon R.; Merkel, Rudolf; Rueger, Maria A.; Hoffmann, Bernd (Frontiers in Cellular Neuroscience, 2021)
The neural stem cell (NSC) niche is a highly vascularized microenvironment that supplies stem cells with relevant biological and chemical cues. However, the NSCs’ proximity to the vasculature also means that the NSCs are subjected to permanent tissue deformation effected by the vessels’ heartbeat-induced pulsatile movements. Cultivating NSCs under common culture conditions neglects the—yet unknown—influence of this cyclic mechanical strain on neural stem cells. Under the hypothesis that pulsatile strain should affect essential NSC functions, a cyclic uniaxial strain was applied under biomimetic conditions using an in-house developed stretching system based on cross-linked polydimethylsiloxane (PDMS) elastomer. While lineage commitment remained unaffected by cyclic deformation, strain affected NSC quiescence and cytoskeletal organization. Unexpectedly, cyclically stretched stem cells aligned in stretch direction, a phenomenon unknown for other types of cells in the mammalian organism. The same effect was observed for young astrocytes differentiating from NSCs. In contrast, young neurons differentiating from NSCs did not show mechanoresponsiveness. The exceptional orientation of NSCs and young astrocytes in the stretch direction was blocked upon RhoA activation and went along with a lack of stress fibers. Compared to postnatal astrocytes and mature neurons, NSCs and their young progeny displayed characteristic and distinct mechanoresponsiveness. Data suggest a protective role of young astrocytes in mixed cultures of differentiating neurons and astrocytes by mitigating the mechanical stress of pulsatile strain on developing neurons.